Three : the human resources emerging executive - Ziskin, Ian, 1958- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Centered around three critical and complementary aspects of the role, this book explores leadership philosophy, HR's evolving role in today's organizations, and the future of HR and effective organizations to help emerging HR leaders find and establish their place in the field. --
The Development of Leadership Capability in Modern Organizations: The Role of the HR ExecutiveBecoming an HR Professional; Notes and References; The HR Executive's Most Crucial Capability? A Strategic Leadership Mindset; References; The Story of HR Courage; CHAPTER 12 Honor HR HeRoes; Lessons Learned on the Playing Field; Top Themes; 1. Business Acumen to Advise and Influence; THREE PulseCheck (After); Epilogue; Appendix 1 Personal Leadership Profile; Appendix 2 Human Capital Strategy Framework; Appendix 3 Performance Culture Assessment; Appendix 4 ZTRON Technologies, Inc. Mini-Case Study.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Personnel management; Personnel directors; Personnel Management; Personnel -- Direction; Directeurs du personnel; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Personnel directors; Personnel management